Natural Shifts in Endosymbionts' Occurrence and Relative Frequency in Their Ciliate Host Population - Flemming, Felicitas E.; Grosser, Katrin; Schrallhammer, Martina (Frontiers in Microbiology, 2022)
The role of bacterial endosymbionts harboured by heterotrophic Paramecium species is complex. Obligate intracellular bacteria supposedly always inflict costs as the host is the only possible provider of resources. However, several experimental studies have shown that paramecia carrying bacterial endosymbionts can benefit from their infection. Here we address the question which endosymbionts occur in natural paramecia populations isolated from a small lake over a period of five years and which factors might explain observed shifts and persistence in the symbionts occurrence. 119 monoclonal strains were investigated and approximately two-third harboured intracellular bacteria. The majority of infected paramecia carried the obligate endosymbiotic “Candidatus Megaira polyxenophila”, followed by Caedimonas varicaedens, and Holospora undulata. The latter was only detected in a single strain. While “Ca. M. polyxenophila” was observed in seven out of 13 samplings, C. varicaedens presence was limited to a single sampling occasion. After the appearance of C. varicaedens, “Ca. M. polyxenophila” prevalence dramatically dropped with some delay but recovered to original levels at the end of our study. Potential mechanisms explaining these observations include differences in infectivity, host range, and impact on host fitness as well as host competitive capacities. Growth experiments revealed fitness advantages for infected paramecia harboring “Ca. M. polyxenophila” as well as C. varicaedens. Furthermore, we showed that cells carrying C. varicaedens gain a competitive advantage from the symbiosis-derived killer trait. Other characteristics like infectivity and overlapping host range were taken into consideration, but the observed temporal persistence of “Ca. M. polyxenophila” is most likely explained by the positive effect this symbiont provides to its host.